Melting Pot Ottakring!? Distinktionsprozesse und Disziplinierungsbestrebungen an den Rändern des Urbanen: Ein Projektbericht - Niederkofler, Heidi; Rajal, Elke (Österreichische Zeitschrift für Geschichtswissenschaften, 2017)
Abstract: Processes of social distinction and disciplining efforts on the urban margins can be explored historically in different areas such as housing and social politics, both communal and private. During a two-year research project, scholars based at the Kreisky-Archive in Vienna, together with students at a local grammar school (Gymnasium Maroltingergasse) have been investigating these phenomena in relation to early twentieth-century Ottakring, a Viennese suburb. The suburbs of the growing metropolis inhabited by the poor were perceived as the ‘other side of civilization’. This view was accompanied by fascination as well as processes of boundary-drawing and stigmatization and the responses led to various interventions into the suburban spaces concerned. In two case-studies the authors analyze such interventions with a focus on the fantasies and fears concerning the suburban ‘other’: The first focuses on the Ottakringer Notstandsbauten, a shanty town for poor workers with many children which was built by the municipal government in 1911 as a reaction to the rampant housing shortage and homelessness in the urban region. The second focuses on the welfare organisation Wiener Settlement, founded in 1901 by members of the liberal women’s movement. The association’s estate, accessible at the Sammlung Frauennachlässe, University of Vienna, was a primary source for examinating the Viennese Settlement. Concerning the Notstandsbauten, interviews with former residents and biographical narratives of former neighbors have been analyzed along with newspaper articles.